Thermosensitive Copolymeric PLGA-PEG-PLGA Nanomicelles of Raloxifene: Synthesis, Formulation, and In-vitro Characterization (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
The objective of the present research study has been to synthesize (PLGA-PEG-PLGA), a thermolabile and biodegradable triblock copolymer. The polymer was subjected to differential evaluation using NMR, XRD, and FTIR techniques for characterization. Raloxifene, a potential therapeutic for breast cancer, exerts poor water solubility and a low fraction of bioavailability owing to its pharmacokinetic properties. The synthesized polymer was used to load raloxifene-encapsulating polymeric micelles, which were then subjected to several evaluations with the aim of improving solubility and bioavailability standards. Zeta potential for the developed formulation was approximately -0.73 mV, indicating a relatively neutral surface charge. It subsequently emerged that the sizes of the blank and raloxifene-loaded micelles were 40.18 and 42.18 nm, respectively. The drug encapsulating capacity and% drug loading capacity were determined to be 73.4 ± 0.34% and drug loading 6.04 ± 0.002% (w/w), respectively. In-vitro study illustrated a 94.37% sustained release drug profile for 120 hours. In this research study, polymeric raloxifene nanomicelles were successfully prepared to enhance solubility, bioavailability, and antitumor effect due to the smaller size of the micelles.